Model tests of consolidation of clay slurry using horizontal drains - Tan, Chelsea Jing Wen (2017)
With a need for land reclamation for political, social and economic needs, Singapore has recently been using marine clay as a new alternative to be self-sufficient in this aspect. However, marine clay is high in water content and low in shear strength and has to be improved as part of the land reclamation process. The aim of this project is to study the effectiveness of using vacuum preloading with prefabricated horizontal drains (PHD) as a treatment method for the consolidation of clay slurry. The pressure from the vacuum pump serves as a preload to dissipate pore water pressure and reduce water content, allowing consolidation to take place. The PHD distributes pressure from the vacuum pump to enhance the pore water dissipation by reducing the drainage path. The consolidation of clay slurry is carried out in a tank. 2 Model Tests of varying PHD spacing are carried out. Each PHD is attached to a vacuum pump – applied pressure of -80kPa – and installed within the clay slurry. Settlement readings and pore water pressure readings – from pressure transducers – were taken at regular intervals during the tests. The properties of clay slurry, including its grade, permeability and void ratio, determined from experiments, are discussed in this paper. Settlement readings recorded are used for the prediction of the ultimate settlement of clay slurry, and thus the degree of consolidation, which is a factor in determining the effectiveness of the treatment method. Pore water pressure readings, which have changes that are largely influenced due to the vacuum pump pressure, are also studied to determine its behaviour at various distances from the PHD. Both the degree of consolidation and pore water pressures for Models 1 and 2 are compared, to study the differences in effectiveness and efficiency of this treatment method.